Evaluation of the Entomopathogenic Fungus Beauveria bassiana on Different Stages of Phlebotomus papatasi (Diptera: Psychodidae), Vector of Zoonotic Cutaneous Leishmaniasis in Iran - Masoumeh Pirmohammadi; Reza Talaei-Hassanloui; Seyed Hassan Moosa-Kazemi; Yavar Rassi; Sara Rahimi; Mahboubeh Fatemi; Marzieh Ghassemi; Mohammad Hossein Arandian; Reza Jafari; Seyedeh Reyhaneh Golzan; Amir Ahmad Akhavan; Hassan Vatandoost (Tehran University of Medical Sciences, 2024)
Background: Zoonotic cutaneous leishmaniasis is a major public health problem in Iran with the main vector of Phlebotomus papatasi. The use of entomopathogenic fungi for biological control of the vector is a potential substitute for the current methods which are being used. The purpose of the current study was to assess the virulence of two local isolates of Beauveria bassiana (OZ2 and TV) against Ph. papatasi. Methods: To perform the bioassay test, fungal suspensions were applied for every stage of the sand fly life cycle. The mortality rate, longevity, and number of eggs laid were determined. Also, the probability of fungal survival on the surface of rodent's body was assessed.  Results: The longevity of infected adult sand flies with both isolates of B. bassiana was significantly lower (P< 0.05) in comparison to the negative control. The estimated Lethal concentration 50 (LC50) values for adult female and male sand flies treated with OZ2 isolate were 1.4×106 and 2.2×107 conidia/ml, respectively, while they were 6.8×106 and 2.3×108 conidia/ml for TV isolate, respectively. Both isolates of B. bassiana exhibited nonsignificant mortality rates in sand fly larvae and pupae and fecundity rate (P> 0.05). According to our findings for both isolates, the fungus continued to spread throughout the surface of the rodent's body for 144 hours after spraying. Conclusion: The current study demonstrated that both isolates of B. bassiana have considerable biological control capacity against adult sand flies.